2x^2-10x+5=2(x^2-5x+5/2)=
=2(x^2-2*x*5/2+(5/2)^2-(5/2)^2+5/2)=
2((x-5/2)^2-25/4+10/4)=2((x-5/2)^2-15/4)=
=2((x-5/2)^2-(sqrt15/2)^2)=
=2(x-5/2-sqrt15/2)(x-5/2+sqrt15/2)=
=2(x-(5+sqrt15)/2)(x-(5-sqrt15)/2)
General case:
P_2(x)=ax^2+bx+c=a(x^2+b/ax+c/a)=
=a(x^2+2*x*b/(2a)+(b/(2a))^2-(b/(2a))^2+c/a)=
=a((x+b/(2a))^2-(b^2-4ac)/(4a^2))=
=a((x+b/(2a))^2-(sqrt(b^2-4ac)/(2a))^2)=
=a(x+b/(2a)-sqrt(b^2-4ac)/(2a))(x+b/(2a)+sqrt(b^2-4ac)/(2a))=
=a(x-(-b+sqrt(b^2-4ac))/(2a))(x-(-b-sqrt(b^2-4ac))/(2a))
You can see that P_2(x)=0 for
x-(-b+sqrt(b^2-4ac))/(2a)=0 => x=(-b+sqrt(b^2-4ac))/(2a)
or
x+(-b+sqrt(b^2-4ac))/(2a)=0 => x=(-b-sqrt(b^2-4ac))/(2a)
which is famous formula for solutions of the quadratic equation.